2020
DOI: 10.3390/su122410646
|View full text |Cite
|
Sign up to set email alerts
|

Novel Magnetic Nano Silica Synthesis Using Barley Husk Waste for Removing Petroleum from Polluted Water for Environmental Sustainability

Abstract: Water contamination by petroleum and its byproducts presents a major challenge worldwide. It is critical that sustainable treatment methods be employed for the removal of such contaminants from polluted water. For this investigation, magnetic nano silica (M-NS) was synthesized using agricultural waste from barley husk using a two-step process that is environmentally friendly and uses green chemistry synthesis. The barley husk waste was used as a precursor for the synthesis of nano-silica following a low energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The world is now dealing with various climatic concerns and deteriorating ecological conditions. This is due to the increasing ecological challenges that are arising as a result of changing lifestyles and economic practices (Essien et al, 2019;Vaseashta et al, 2020). According to BP data, global total CO 2 emissions from fossil energy reached 33,890.8 million tonnes in 2018, up from 11,190 million tonnes in 1965.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The world is now dealing with various climatic concerns and deteriorating ecological conditions. This is due to the increasing ecological challenges that are arising as a result of changing lifestyles and economic practices (Essien et al, 2019;Vaseashta et al, 2020). According to BP data, global total CO 2 emissions from fossil energy reached 33,890.8 million tonnes in 2018, up from 11,190 million tonnes in 1965.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change presents a danger to people's lives and livelihoods. Pollution and extreme weather events, which are frequently observed, cause substantial threats to human beings (Farooq et al, 2019;Vaseashta et al, 2020;Akhayere and Kavaz, 2021;Fareed et al, 2021). In this regard, it is important to enhance public knowledge about environmental issues; otherwise, the risks and threats connected with climate change, which are expected to increase in the coming years, will have devastating implications for human safety and health.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the pore volume, pore width, and specific surface area were improved in MTBC rather than TBC. This indicates that Fe (NO 3 ) 3 modification supports the formation of pores during pyrolysis [ 28 ]. Figure 1 display the N 2 adsorption–desorption graph of prepared adsorbents with their pore desorption distribution by BJH analysis (Barrett Joyner Halenda).…”
Section: Resultsmentioning
confidence: 98%
“…In our environment, wastes are generated from different sectors on a daily basis and the agricultural sector produces large amounts of waste. Dietary fiber, animal manure, risk husk, banana peels, coconut shell, and tea are the important wastes that belong to the agricultural sector [ 28 ]. Tea is the most widely used beverage, with nearly 3.5 million tons of tea being used per year globally [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high concentrations can cause the skin to turn blue or gray and more serious health effects like weariness, weakness, and dizziness. 21 Nitrate levels in drinking water might be low as a result of natural processes. Water alterations Lowering the total nitrate level in the aquarium can be accomplished by doing routine water changes using water that contains little to no nitrate.…”
Section: Discussionmentioning
confidence: 99%